2002
DOI: 10.2166/ws.2002.0105
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different advanced disinfection systems for wastewater reclamation

Abstract: Several lines of reclamation have been tested in the Palamós/Vall-Llobrega (Girona, Spain) wastewater treatment plant. Each line consists of a filtration treatment (infiltration-percolation, sand filter, ring filter and physico-chemical treatment) plus a disinfection system (UV, peracetic acid, chlorine dioxide and ozonation). Every combination has been evaluated and compared with the other possibilities. This combination of filtration and disinfection allows the use of lower doses of disinfectants, thus minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…PAA is considered to be the main active component in the solution (Baldry, 1983;Baldry and French, 1989;Fraser et al, 1985;Kitis, 2004;Lubello et al, 2002). The disinfection efficiency of PAA in wastewater applications has been demonstrated numerous times in the literature (Antonelli et al, 2006;Baldry, 1983;Baldry and French, 1989;Baldry et al, 1991;Baldry et al, 1995;Briancesco et al, 2005;Collivignarelli et al, 2000;Dell'Erba et al, 2004;Gehr et al, 2003;Kitis, 2004;Koivunen and Heinonen-Tanski, 2005a;Koivunen and Heinonen-Tanski, 2005b;Lefevre et al, 1992;Liberti and Notarnicola, 1999;Liberti et al, 1999;Salgot et al, 2002;Veschetti et al, 2003;Zanetti et al, 2007). As a result, PAA is gaining acceptance as a disinfectant, especially in the United Kingdom and Italy (Falsanisi et al, 2006 A recent study by Azzellino et al (2011) showed that PAA disinfection is more dependent on dosage than on contact time.…”
Section: Introductionmentioning
confidence: 99%
“…PAA is considered to be the main active component in the solution (Baldry, 1983;Baldry and French, 1989;Fraser et al, 1985;Kitis, 2004;Lubello et al, 2002). The disinfection efficiency of PAA in wastewater applications has been demonstrated numerous times in the literature (Antonelli et al, 2006;Baldry, 1983;Baldry and French, 1989;Baldry et al, 1991;Baldry et al, 1995;Briancesco et al, 2005;Collivignarelli et al, 2000;Dell'Erba et al, 2004;Gehr et al, 2003;Kitis, 2004;Koivunen and Heinonen-Tanski, 2005a;Koivunen and Heinonen-Tanski, 2005b;Lefevre et al, 1992;Liberti and Notarnicola, 1999;Liberti et al, 1999;Salgot et al, 2002;Veschetti et al, 2003;Zanetti et al, 2007). As a result, PAA is gaining acceptance as a disinfectant, especially in the United Kingdom and Italy (Falsanisi et al, 2006 A recent study by Azzellino et al (2011) showed that PAA disinfection is more dependent on dosage than on contact time.…”
Section: Introductionmentioning
confidence: 99%
“…PAA is advantageous over ozone especially when the need to disinfect is irregular. The operation and maintenance costs of ozone system (at a dose of 15 mg/L) has been calculated to be lower than with PAA (at a dose of 10 mg/L) [127].UV has often been concluded to be more effective in terms of disinfection efficiency [124,127].However, the physico-chemical quality of wastewater has a strong effect on UV disinfection efficiency and consequently PAA and UV have been occasionally reported to be also more or less similar in terms of efficiency [125,126]. For example, when disinfecting primary effluent, …”
mentioning
confidence: 99%
“…[138]. The combination of tertiary treatment and disinfection can be referred to as the multiple barrier concept, which has been shown to be the most effective approach for disinfection [126,127]. The required doses and contact times for the disinfection of secondary effluents with PAA vary within the range of 0.6-10 mg/L and 10-60 mins, respectively (see Table 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Salgot et al (2002), different filtration and disinfection processes significantly reduce the chemical oxygen demand (COD), BOD, and fecal coliforms. They also found that the combination of UV and ozone was more effective for disinfection of wastewater than other treatments.…”
Section: Resultsmentioning
confidence: 99%